1996
DOI: 10.1074/jbc.271.51.33054
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Expression of Two Novel Avian Cytochrome P450 1A Enzymes Induced by 2,3,7,8-Tetrachlorodibenzo-p-dioxin

Abstract: Transcriptional regulation by the aryl hydrocarbon receptor, for which the environmental toxin 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) is the most potent ligand, leads in mammalian liver to the induction of genes for two distinct cytochrome P450 (CYP)1A enzymes, CYP1A1 and -1A2. Fish seem to have only one CYP1A enzyme. CYP1A enzymes have been regarded as injurious largely because of their ability to activate chemical carcinogens. We report here the cloning and sequencing of cDNAs for two catalytically disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(60 citation statements)
references
References 26 publications
0
60
0
Order By: Relevance
“…1B). Concurrently, TCDD increased expression of major AHR target genes, CYP1A4 and CYP1A5, chick orthologs of mammalian CYP1A1 and 1A2, respectively (25). Effects in ovo were seen as early as 12 h after treatment (not shown) and were sustained for at least 96 h (Fig.…”
Section: -Ethoxyresorufin-o-deethylase (Erod)-erodmentioning
confidence: 93%
“…1B). Concurrently, TCDD increased expression of major AHR target genes, CYP1A4 and CYP1A5, chick orthologs of mammalian CYP1A1 and 1A2, respectively (25). Effects in ovo were seen as early as 12 h after treatment (not shown) and were sustained for at least 96 h (Fig.…”
Section: -Ethoxyresorufin-o-deethylase (Erod)-erodmentioning
confidence: 93%
“…The fact that this orthology is not reflected in traditional phylogenetic analyses (e.g. Gilday et al, 1996a) may be attributed to concerted evolution via inter-paralog gene conversion.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analyses of nucleic acid and amino acid sequences show that chicken CYP1A4 and CYP1A5 cluster together, separately from the mammalian CYP1A1/1A2 clade (Gilday et al, 1996b). This has been interpreted to mean that CYP1A4 and CYP1A5 resulted from an independent gene duplication that occurred subsequent to the divergence of the avian and mammalian lineages.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work from this laboratory showed that TCDD-induced CYP1A4 is entirely responsible for the increased 7-ethoxyresorufin deethylase (EROD) activity and CYP1A5 for the increased epoxygenation of the endogenous membrane fatty acid, arachidonic acid (aa), in chick embryo (CE) liver microsomes [9][10][11]. Further, TCDD treatment suppressed formation of another P450 aa metabolite, 20-HETE, in both mammalian and CE liver microsomes [12,13].…”
Section: Introductionmentioning
confidence: 99%